Heavy metals in cowpea (Vigna unguiculata L.) after tannery sludge compost amendment - Silva, Maria Doroteia Marcal; Araujo, Ademir Sergio Ferreira; Nunes, Luis Alfredo Pinheiro Leal; Melo, Wanderley Jose de [UNESP]; Singh, Rajeev Pratap (Inst Investigaciones Agropecuarias, 2013)
Repeated soil amendment with industrial waste can affect the accumulation of chemical elements, mainly heavy metals, in plants. We therefore evaluated the accumulation of Cr, Cd, Ni, and Pb in cowpea (Vigna unguiculata [L.] Walp.) shoots and grains in soil amended for three consecutive years with tannery sludge compost (TSC). Tannery sludge compost was applied annually starting in 2009 at 0, 2.5, 5, 10, and 20 t ha(-1) and cowpea was sown. At 40 and 60 d after cowpea sowing, the accumulation of Cr, Cd, Pb, and Ni was evaluated in the shoots and grains, respectively. The experiment used completely randomized design with four replicates and data were subjected to ANOVA and F-test (5%). Only Cr accumulation was significant (P < 0.05) in the cowpea shoots after 3 yr of TSC amendment; accumulation increased as TSC rates were applied. However, there was no significant Cr, Cd, Ni, and Pb accumulation in grains. After 3 yr of consecutive TSC soil amendments, Cr accumulated in the shoots, but it was not translocated to the grains.
Keywords: Organic residue; trace elements; Vigna unguiculata